Modification of Microstructure and Properties of Martensitic Stainless Steel by High-Intensity Implantation of Nitrogen Ions - Korneva O. S. Olga Sergeevna; Ryabchikov A. I. Aleksandr Ilyich; Sivin D. O. Denis Olegovich; Bozhko I. A. Irina Aleksandrovna; Koval T. V. Tamara Vasilievna; Ivanova A. I. Anna Ivanovna; Stepanov I. B. Igor Borisovich (Ion Beam Processing of Materials. Poster Session, 2019)
Заглавие с экрана